HUBUNGAN PENGETAHUAN BANTUAN HIDUP DASAR DENGAN MOTIVASI PADA POLISI LALU LINTAS DALAM KORBAN KECELAKAAN LALU LINTAS DI POLRESTA AMBON - Harianti Fajar; Lina Malaiholo; Dwight Nusawakan (STIKES Pasapua Ambon, 2021)
Introduction: In order to realize an increase in the quality of services in handling emergency victims, a victim handling system is needed that is carried out in an integrated and integrated manner involving several parties. So that the traffic police are included in services for the community when traffic accidents occur because they are the first helpers other than the community. Handling is carried out with basic life support, it is important for the police to have high motivation in helping accident victims with basic life support. The purpose of this research is to find out whether there is a relationship between knowledge of basic life support and the motivation of the traffic police in providing assistance to traffic accident victims at the Ambon Police. Method: The research method used is descriptive with a cross sectional design. The research sample was taken using a purposive sampling technique with a total sample of 44 respondents. Bivariate analysis using fisher’s exact test. Results: The research results obtained were that some traffic police in the city of Ambon with good basic life support knowledge were 32 respondents or 96.9% with 31 respondents with high motivation and 1 respondent with low motivation. There is a relationship between basic life support knowledge (BHD) and the motivation of the traffic police in providing assistance to victims of traffic accidents in the city of Ambon with a P-value of 0.004. Conclusion: This study indicate that most of the traffic police have good knowledge of basic life support and have high motivation in helping traffic accident victims.